Hazardous radioactivity levels and heavy mineral concentrations in beach sediments of Lake Peipsi, northeastern Estonia - Järvelill, Johanna-Iisebel; Koch, Rein; Raukas, Anto; Vaasma, Tiit (Geologos, 2018)
The present study discusses results of heavy mineral analyses and radioactivity of beach sediments of Lake Peipsi. Such analyses are commonly done globally, but had not yet been conducted for the fourth largest lake in Europe. The average heavy mineral content in Lake Peipsi beach sediments along the northern and western coast is higher than usual for Estonian coastal and Quaternary sediments. Concomitantly, elevated radioactivity levels have been measured in several places, with the highest concentrations observed at Alajõe (1885.5 Bq/kg), which is over five times more than the recommended limit. The aim of the present study is to find sites with higher radioactivity levels, because the northern coast of Lake Peipsi is a well-known recreational area.